Optimum Coherent and Incoherent Demodulators of BPSK and DBPSK Radio Signals with Manchester Encoding - В. Г. Парфенюк; С. С. Сабадаш; Р. Л. Ставісюк (Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni Kììvsʹkij Polìtehnìčnij Ìnstitut: Serìâ Radìotehnìka, Radìoaparatobuduvannâ, 2021)
Algorithms and schemes of optimal coherent and incoherent demodulators of binary radio signals with phase and differential phase shift-keying (DPSK) with Manchester encoding of the modulating signal are proposed. The use of DPSK makes it possible to effectively deal with the phase ambiguity of the reference oscillation generator of the correlation receiver. This solution allows you to overcome the so-called <<reverse work>> effect in the demodulator of signal with phase-shift keying. Differential and Manchester encoding finds it's application in various areas of use of digital systems for information transmission (DSIT): from local and personal area networks, to space optical communication systems. There are many types of DSIT: radio communication systems (in the Bluetooth standards, in NFC technology, as well as in high-resolution space remote sensing (SRS)), wired data transmission systems (in the local area networks of the Ethernet family), so are optical communication systems (FSO, ISOWC and SpaceWire). It's shown that the joint use of DPSK and Manchester encoding provides higher noise immunity when used in DSIT and retain the advantages of Manchester encoding with respect to symbolic synchronization of the demodulator. The given algorithms and schemes are based on the use of reception in general and the features of Manchester encoding, which allows using the full energy of the information bit for demodulation. To assess the potential noise immunity of the proposed demodulator schemes, it's assumed that the modulated signals are orthogonal in the amplified sense. The conducted mathematical modeling of the proposed technical solutions confirmed their operability and higher noise immunity compared to the symbol-by-symbol reception. It's proposed to use the developed algorithms and schemes of demodulators in the receivers of the SRS with high resolution, in the receivers of optical communication systems and in the receiving part of the equipment of local networks of the Ethernet family.